Exploring participation of IIUM Kuantan students in walking as a physical activity - Adnan, Nur Amirah Aqilah; Mohamad, Mohd Yusof (https://journals.iium.edu.my/ijahs/index.php/IJAHS/article/view/882/781, 2023)
Introduction: Walking is one of the physical activities that benefits people of all ages. The main objective of this study is to determine the participation in walking among IIUM Kuantan students and comparison with other physical activities. Method: The study was conducted by distributing an online google form questionnaire to all undergraduate IIUM Kuantan students via an online survey. 80 of the respondents participated in the study based on inclusion and exclusion criteria. Result: The outcome of the research regarding frequency and duration of walking was within average number of 5 days per week and 30 minutes duration per day. Conclusion: The adherent to simplest physical activity such as walking needs to be empowered to ensure the long-term applicability and benefits. However, the gender differences portrayed no significant difference between male and female respondents in walking activity. In terms of physical activity, walking was found to have the highest participation among IIUM students as compared to moderate and vigorous physical activity.